Modernist Literary-Criticism in Indonesia: A Study on the Practices of Millenial Digital Literacy on the Youtube Comments - Johan Mahyudi; Ahmad Sirulhaq (Bina Nusantara University, 2023)
The research was focused on investigating the tradition of modernist literary criticism, which could be found in the audience’s comments under the video on the YouTube website. As the center of the digital literary paradigm, digital poetry in videography has become an object of criticism for the Indonesian millennial generation. As was known, one of the markers of digital literacy was proficiency in using digital media. One of these media was used to produce criticism by voicing non-text semiotics. Because of that, in the research, thousands of criticisms that appeared on the poetry websites “Aksara Betha” and “Rotasi” were analyzed by reviewing examples of the critics’ expressions of non-text elements that could be found in the constructs of the two digital poetry. The results show that Indonesian millennials are digitally literate, and many explicitly mention digital art features that have attracted their interest. Some critics even express their subjective feelings about the show’s duration which is considered too short. Such practice explains that the Indonesian millennial generation has felt the effect of one of the morphological elements of digital poetry, namely space and time. Furthermore, suppose it can be called a tradition; in that case, the honesty of the critics in collecting criticism of the work they prepare is the milestone of the new tradition in literary criticism. This tradition is rarely, if not never, to be found in the tradition of printed literary criticism.